Diluted Blood Still Better than Water? The Beneficial Effects of Politicians' Birthplaces on Refugee Acceptance - Hai-Anh Dang; Trong-Anh Trinh (Institute of Labor Economics (IZA), 2023)
In parliamentary systems, elected representatives often have power to direct resources to their preferred areas. Foreign-born politicians, those who were born in countries other than the country where they hold policymaking positions, may exhibit a strong preference for refugees. We provide the first empirical evidence on the relationship between politicians' birthplaces and refugee acceptance. Employing an instrumental variable approach to analyze a newly-constructed panel data set comprising 17 destination countries in the OECD during 2002-2019, we find that countries with higher shares of foreign-born politicians have higher recognition rates and offer more aid to refugees. Our findings remain robust for different outcome variables, model specifications, and birthplaces' income levels. Some evidence also suggests that countries with more foreign-born politicians affiliated with left-wing parties tend to show more favouritism toward refugees. Finally, we find that favourable asylum policy and positive public opinion are possible explanations for increased acceptance of refugees.
Keywords: F22; F35; D72; O15; 330; foreign-born politician; refugee acceptance; recognition rate; refugee aid; asylum policy